2021
DOI: 10.3390/ijms22020866
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Intestinal Phosphate Transport in Young Goats Fed a Low Phosphorus Diet

Abstract: The intestinal absorption of phosphate (Pi) takes place transcellularly through the active NaPi-cotransporters type IIb (NaPiIIb) and III (PiT1 and PiT2) and paracellularly by diffusion through tight junction (TJ) proteins. The localisation along the intestines and the regulation of Pi absorption differ between species and are not fully understood. It is known that 1,25-dihydroxy-vitamin D3 (1,25-(OH)2D3) and phosphorus (P) depletion modulate intestinal Pi absorption in vertebrates in different ways. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…In this study, the highest expression levels of intestinal P transport-related genes were found in spotted seabass fed the diet with an available P level of 0.35%. P deficiency has also been found, in other studies, to cause the upregulation of genes related to P transport [46]. Combining the results of the ADC of P and whole-body P deposition efficiency, it is hypothesized that this can be a regulatory mechanism for the perch to adapt to the P-deficient environment by improving the absorption, utilization and deposition of P.…”
Section: Discussionmentioning
confidence: 60%
“…In this study, the highest expression levels of intestinal P transport-related genes were found in spotted seabass fed the diet with an available P level of 0.35%. P deficiency has also been found, in other studies, to cause the upregulation of genes related to P transport [46]. Combining the results of the ADC of P and whole-body P deposition efficiency, it is hypothesized that this can be a regulatory mechanism for the perch to adapt to the P-deficient environment by improving the absorption, utilization and deposition of P.…”
Section: Discussionmentioning
confidence: 60%
“…N-reduced feeding had no effect on these parameters. The data on P-reduction were partially published by Behrens et al [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Muscher and Huber (4), N-reduction also resulted in alterations in vitamin D metabolism. P-reduction also resulted in modulation of mineral homeostasis in goats and sheep with reduced plasma concentration of P i and concomitant high plasma Ca levels in the blood (6,7). The homeostasis of P i and Ca in the body is tightly regulated by various hormones, primarily controlled by the interaction of active vitamin D (1,25(OH) 2 D 3 , calcitriol), parathyroid hormone (PTH), and fibroblast growth factor 23 (FGF23) (8).…”
mentioning
confidence: 99%